2021
DOI: 10.3390/pr9030499
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Dynamic Stresses of Pump-Turbine Runner during Start Up in Turbine Mode

Abstract: The startup process occurs frequently for pumped storage units. During this process, the rotating rate that changes rapidly and unsteady flow in runner cause the complex dynamic response of runner, sometimes even resonance. The sharp rise of stress and the large-amplitude dynamic stresses of runner will greatly shorten the fatigue life. Thus, the study of start-up process in turbine mode is critical to the safety operation. This paper introduced a method of coupling one dimensional (1D) pipeline calculation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…However, RSI will greatly increase the dynamic stress as load increases, and becomes the dominant hydraulic phenomenon up to overload of a high head Francis turbine runner [19]. A similar phenomenon was also found in a pump-turbine runner [20]. In addition, a study on the dynamic stress characteristics of a Francis turbine runner show that dynamic stress is one of the main reasons for fatigue and cracking of the blade [21].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, RSI will greatly increase the dynamic stress as load increases, and becomes the dominant hydraulic phenomenon up to overload of a high head Francis turbine runner [19]. A similar phenomenon was also found in a pump-turbine runner [20]. In addition, a study on the dynamic stress characteristics of a Francis turbine runner show that dynamic stress is one of the main reasons for fatigue and cracking of the blade [21].…”
Section: Introductionmentioning
confidence: 64%
“…The present work investigates effects of operating head on the dynamic response characteristics of a pump-turbine runner in turbine mode using the weak fluid-structure coupling method (i.e., the effects of deformation of the runner on flow characteristics of the pump-turbine are small, so we only consider the effects of flow characteristics on the dynamic response of the runner). This method has been widely adopted in the literature, and its reliability on pump-turbine models has been verified [8,19,20,28,29]. The two-way coupling method is closer to the real condition, but it requires very high computing resources.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the pump turbine can operate flexibly to adjust the grid load, which means the pump turbine needs to work at the lower operating point and undergo frequent transition processes. A large number of experiments and simulation studies have been carried out to study the flow field and structural field characteristics of the pump turbine [1][2][3][4][5]. Some studies have included a wearing ring, because the clearance flow on the crown and near the band has been shown to have a significant effect on hydraulic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that different factors such as the disturbance intensity and the slope of the no-load working point have different effects on no-load stability. Chen et al 9 studied the variation process of pulsating pressure in runner area during start-up process based on 1D-3D coupling models. Fahlbeck et al 10 analyzed the flow characteristics under emergency shutdown and start-up condition.…”
Section: Introductionmentioning
confidence: 99%